Transcatheter aortic valve implantation vs. surgical aortic valve replacement for treatment of severe aortic stenosis: a meta-analysis of randomized trials - Siontis, George C.M.; Praz, Fabien; Pilgrim, Thomas; Mavridis, Dimitris; Verma, Subodh; Salanti, Georgia; Søndergaard, Lars; Jüni, Peter; Windecker, Stephan (European heart journal, 2016)
In view of the currently available evidence from randomized trials, we aimed to compare the collective safety and efficacy of transcatheter aortic valve implantation (TAVI) vs. surgical aortic valve replacement (SAVR) across the spectrum of risk and in important subgroups. Trials comparing TAVI vs. SAVR were identified through Medline, Embase, and Cochrane databases. The primary outcome was death from any cause at 2 years. We performed random-effects meta-analyses to combine the available evidence and to evaluate the effect in different subgroups. This systematic review and meta-analysis is registered with PROSPERO (CRD42016037273). We identified four eligible trials including 3806 participants, who were randomly assigned to undergo TAVI (n = 1898) or SAVR (n = 1908). For the primary outcome of death from any cause, TAVI when compared with SAVR was associated with a significant 13% relative risk reduction [hazard ratio (95% CI): 0.87 (0.76-0.99); P = 0.038] with homogeneity across all trials irrespective of TAVI device (P = 0.306) and baseline risk (P = 0.610). In subgroup analyses, TAVI showed a robust survival benefit over SAVR for patients undergoing transfemoral access [0.80 (0.69-0.93); P = 0.004], but not transthoracic access [1.17 (0.88-1.56); P = 0.293] (P = 0.024) and in female [0.68 (0.50-0.91); P = 0.010], but not male patients [0.99 (0.77-1.28); P = 0.952] (P = 0.050). Secondary outcomes of kidney injury, new-onset atrial fibrillation, and major bleeding favoured TAVI, while major vascular complications, incidence of permanent pacemaker implantation, and paravalvular regurgitation favoured SAVR. Compared with SAVR, TAVI is associated with a significant survival benefit throughout 2 years of follow-up. Importantly, this superiority is observed irrespective of the TAVI device across the spectrum of intermediate and high-risk patients, and is particularly pronounced among patients undergoing transfemoral TAVI and in females.